Factors Affecting Pharmaceutical Care Implementation by Community Pharmacist: A Discrete Choice Experiment - Nia Kurnia Sholihat; Masita Wulandari Suryoputri; Ade Martinus (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Even though pharmaceutical care has been proven increasing patients’ quality of life, pharmacists still have barriers to implement it. Our study aims to examine factors affecting pharmacists in the community to implement pharmaceutical care using a Discrete Choice Experiment (DCE). The study was a cross-sectional study. A structured DCE questionnaire was administered to 90 community pharmacists in Banyumas district, Indonesia. Respondents were chosen using a simple random sampling method. According to the literature review and expert opinions, the following six attributes were selected: pharmacists’ confidence; willingness to implement pharmaceutical care; communication skill; knowledge and professional skill; availability of time; and availability of space in pharmacy. Eighteen choice sets were developed. Each choice sets comprised of two scenarios. Respondents were asked to choose the scenario they preferred the most. Data were analyzed using multinomial logit model. Of 90 questionnaires distributed, 67 were analyzed. Based on multinomial logit, all attributes had a significant effect on pharmacists’ preferences to implement pharmaceutical care. The findings suggested that pharmacist association should train their member to increase professional skills, as well as the management of pharmacy should provide enough space to perform pharmaceutical care.